Analisis terhadap Kewajiban Notaris Membacakan Akta dihadapan Penghadap menurut Pasal 16 Ayat (1) Huruf L Undang-Undang No. 2 Tahun 2014 Tentang Jabatan Notaris - Mellinia Dilla Wardhani; Aisyah Ayu Musyafah (LPPM Universitas Ekasakti Padang, 2023)
The making of an authentic deed from a notary is not based solely on existing regulations but is the wish of each related party so that there is certainty regarding the rights and obligations they have. A notary who does not read out the deed that has been made may be subject to punishment in accordance with Article 16 paragraph 9 UUJN. In its implementation (Das Sein), there are Notaries who often do not read the notes they have made even though in the last sentence they say it is explained that what has been made has been read out by the Notary concerned. This raises new problems and makes the roof related to a deed under the hand and makes the party who wants it loses. The research to be carried out is a type of normative legal research through the study of literature and other legal materials, for example related to legal principles, positive law, legal principles and also the rule of law. The results of the study show that according to article 16 paragraph 1 letter (m) UUJN which explains that a notary is required to read every deed that has been made before the appearers and the legal consequences of a deed that are not in accordance with Article 16 paragraph 1 letter (1) UUJN are deed that made with a stamp or stamp that includes the symbol of the Unitary Republic of Indonesia and in a circular space the name, position and location of office of the relevant notary who makes the deed a private deed are stated in the circular space. This makes assets unable to be used according to the interests facing which of course makes the related parties lose money.